"Of Course I Can": The Effect of CEO Overconfidence on Entrepreneurially Oriented Firms. (3rd March 2014) - Engelen, Andreas; Neumann, Christoph; Schwens, Christian
<x xml:space="preserve">Abstract</x> Guided by the upper echelons theory, this research examines the relationship between chief executive officer (CEO) overconfidence and a firm's entrepreneurial orientation (EO). The study theoretically establishes and empirically validates an increasing effect of CEO overconfidence on EO, although at a decreasing rate. Empirical results are based on a multisource secondary data set for high‐tech S&P 500 firms from 2005 to 2007. Findings further indicate that the proposed relationship between CEO overconfidence and EO is moderated by market dynamism. A theoretically established moderating effect of market concentration could not be validated empirically.